Sustainable building material-using organic matter focusing on ceiling - Mohd Zulkifly Bin Mohd Shariff (School of Environmental Engineering University Malaysia Perlis, 2011)
Sustainable development is development that meets the needs of the present without compromising the ability of future generation to meet their own needs (World Commission on Environment and Development, 1987). Agriculture waste such as rice straw and rice husk is produced as bio product of rice cultivate. Soil incorporation and field burning have been major practices for removing of rice straw but is now tightly regulated. Burning this agricultural wastes can lead to air pollution, thus causing global warming, ozone depletion and others. In addition, thowring this agricultural waste into animal health, agricultural and others. Thus, this project aims to reduce agricultural waste, with a quality product from this waste, thus can be commercialized in conventional and international trade. The product was tested in 4 parameters which are tensile strenght,flexural strenght, impact strenghtand swelling test (simulation & degradation)